ANALISIS METRIK INTERAKSI TERHADAP PERTUMBUHAN PENGIKUT AKUN INSTAGRAM ITBSS MELALUI MEDIASI JANGKAUAN: PENDEKATAN SEM PLS: ANALYSIS OF ENGAGEMENT METRICS ON ITBSS INSTAGRAM ACCOUNT FOLLOWER GROWTH THROUGH REACH MEDIATION: AN SEM-PLS APPROACH - Melyanto Melyanto (LPPM Universitas Abdurrab, 2026)
Marketing in the era of digital transformation has shifted conventional marketing strategies toward digital marketing, particularly within the education sector. A primary objective in digital marketing is increasing brand awareness. Educational institutions could implement digital marketing strategies by leveraging Instagram analytical data as a data driven decision-making. Interaction is one of the key metrics used by Instagram to determine content ranking and reach. Interaction comprises several actions which are likes, comments, saves, and shares. High post reach can drive visibility and potentially attract new followers. Consequently, this study aims to analyze the influence of these interaction metrics on follower growth for the ITBSS Instagram account as the dependent variable, with reach acting as the mediating variable. The findings indicate that shares have a significant influence on both reach (p-value= 0.000) and follow (p-values= 0.014). Furthermore, likes also significantly influence reach (p-value= 0.000). Comments and saves showed less significant results toward both reach and follow (p-value < 0,05). Reach has no significant in relation to follow (p-value = 0,357). These results provide valuable insights regarding interaction metrics, likes and shares. Instagram content creation should focus on encouraging likes and shares to effectively expand content reach and acquire new followers.